2018
DOI: 10.1177/105268461802800403
|View full text |Cite
|
Sign up to set email alerts
|

Journey of a Culturally Responsive, Socially Just Leader

Abstract: Principals' beliefs and actions have powerful outcomes in the lives of the students and families they serve. In this article, we offer the portrait of a long-standing principal of a diverse urban school where the student body is 90% Latinx, 65% English learners (ELs), and 87% eligible for free or reduced-price lunch. We explore many key practices cultivated during his tenure, including creating a bilingual campus, enacting expeditionary-style learning, and building a strong sense of community. We invite reader… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(28 citation statements)
references
References 34 publications
0
1
0
Order By: Relevance
“…First on the agenda were brief selfre-introductions, a review of the group agreements, a review of the cooperative learning roles and the handout for self-assessment of one's cooperative learning role, a review of the process for the written reflection and the discussion-board post. The topics and corresponding anchor readings for CC#2 were: culturally responsive pedagogy (Ladson-Billings, 1995) and Funds of Knowledge (Moll et al, 1992(Moll et al, /2005); for CC#3 the topic and related anchor readings focused on what CSSJP may look like in practice (Newcomer, 2019;Newcomer & Cowin, 2018); and CC#4 focused on a reflection on the CCs process and revisiting all six articles. The sessions were video recorded with transcription available.…”
Section: Methodsmentioning
confidence: 99%
“…First on the agenda were brief selfre-introductions, a review of the group agreements, a review of the cooperative learning roles and the handout for self-assessment of one's cooperative learning role, a review of the process for the written reflection and the discussion-board post. The topics and corresponding anchor readings for CC#2 were: culturally responsive pedagogy (Ladson-Billings, 1995) and Funds of Knowledge (Moll et al, 1992(Moll et al, /2005); for CC#3 the topic and related anchor readings focused on what CSSJP may look like in practice (Newcomer, 2019;Newcomer & Cowin, 2018); and CC#4 focused on a reflection on the CCs process and revisiting all six articles. The sessions were video recorded with transcription available.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, this study identified strategies and challenges to leading for social justice in the specific context of predominantly white suburban schools. Much of the research on social justice leadership in public schools took has taken place in the context of large, urban school districts (Carpenter, Bukoski, Berry, & Mitchell, 2017;DeMatthews & Izquierdo, 2017;Goddard, Skrla, & Salloum, 2017;Newcomer & Cowin, 2018;Shields & Hesbol, 2020;Sun, 2019;Wang, 2016). These school environments historically educate a diverse student population.…”
Section: Significancementioning
confidence: 99%
“…However, in some schools, including students with disabilities or non-native English speakers does not happen regularly. Principals leading for social justice actively eliminate existing practices and structures that are discriminate against students who belong to marginalized groups (Newcomer & Cowin, 2018;DeMatthews & Izquierdo, 2017).…”
Section: Raise Student Achievementmentioning
confidence: 99%
See 2 more Smart Citations